Constructal design of horizontal fins to improve the performance of phase change material rectangular enclosures. (5th December 2015) - Kalbasi, Rasool; Salimpour, Mohammad Reza
Abstract: Invoking phase change material (PCM) based heat sinks as a technique for thermal management is an appropriate cooling scheme for transient or short term applications. The latent heat of the most PCMs is desirably high but the thermal conductivity is unacceptable. This issue can be improved by incorporating high conductive fins into the PCM based heat sink. The purpose of the current study is to determine the effect of adding horizontal fins to improve the efficiency of a heat sink. The required time for the maximum temperature of the heat sink to reach its critical value is maximized invoking constructal theory. Degrees of freedom are the number of enclosures, horizontal fins number and heat sink aspect ratio, while the entire surface area and the PCM content are constraints. The results indicate that the best maximum safe operation time occurs in an optimum value for the horizontal fins number. The results show that for low number of enclosures, heat sinks with high aspect ratios are superior; while, for high number of enclosures, heat sinks with low aspect ratios have better performance. Moreover, adding geometrical complexities to the heat sink will not necessarily improve the performance of the enclosure. Highlights: Effect of adding horizontal fins on the efficiency of a PCM heat sink is studied. There is in an optimum horizontal fins number at which operation time is maximized. Adding complexities to the heat sink will not necessarily improve the performance.